Knowledge Analysis of Biology Education Study Program Students, STKIP Asy-Syafi'iyah International Medan about Laboratory Equipment and Their Functions - Irda Wahidah Nst; Yossie Ulfa Nuzalifa; Nadriyah (PT Inovasi Pratama Internasional, 2022)
In essence, biology education is built on the basis of scientific products, scientific processes, and scientific attitudes. The implementation of practicum activities requires facilities and infrastructure as well as subject matter related to practicum activities. The method used in the implementation of the research is descriptive research. Descriptive research is research conducted to determine the value of independent variables, either one or more variables without making comparisons or connecting one variable to another. This study is a research that seeks to answer the question. The location of the research was carried out at the Biology Education Laboratory, STKIP Asy-Syafi'iyah International Medan Jl. Farmer's Work. The subjects of this study were students of the biology education study program at STKIP Asy-Syafi'iyah Internasional Medan in fifth semester of the Academic Year 2021/2022. The laboratory owned by the STKIP Asy-Syafi'iyah International Medan biology education study program consists of only one room. All practical activities are carried out in this room. Biological laboratories recorded until 2016 had approximately 35 types of laboratory equipment consisting of a set of glassware, teaching aids, preparations, electronic devices, tools made of wood or plastic as well as digital and conventional tools. The design of the laboratory is still very simple, the space is only filled with 6 work desks, 20 work chairs that are not up to standard in the laboratory, 2 storage cabinets for tools and materials, a sink and cleaning equipment. The laboratory of STKIP Asy-Syafi'iyah International Medan is led by a head of the laboratory.